Hypoglycemic and hypolipidemic effects of Nelumbo nucifera flower in Long-Evans rats - Dipa Islam; Amdadul Huque; Sheuly; Liton Chandra Mohanta; Sadhan Kumar Das; Abida Sultana; Evena Parvin Lipy; U. K. Prodhan (Shahrekord University of Medical Sciences, 2018)
Introduction: The study was conducted to assess the hypolipidemic and hypoglycemic effects of Nelumbo nucifera flowers powder in Long-Evans rats. Methods: Experimental rats were made hyperlipidemic and diabetic (type 2) by feeding high fat diet (Lab diet, Dalda and Coconut oil = 4: 3: 1) and injecting alloxan respectively. N. nucifera flowers powder in different percentages was mixed with the regular Lab Diet for 21 days feeding. Serum total cholesterol, triglyceride, low-density lipoprotein (LDL), high-density lipoprotein (HDL) and blood glucose levels were evaluated in various groups. Results: Feeding with N. nucifera flowers powder at different percentages to hyperlipidemic groups showed diverse but a significant (P < 0.05) decrease in serum total cholesterol, triglyceride and LDL-cholesterol levels when compared to control group while HDL-cholesterol level was increased significantly (P < 0.05). Routine feeding with N. nucifera flowers powder for 21 days resulted in significant decrease in the blood glucose levels of alloxan-induced diabetic rats. Both 20% and 10% of N. nucifera flower powders with Lab Diet significantly (P < 0.05) decreased blood glucose level up to 48% and 34%, respectively in comparison to the drug control group treated with glibenclamide which was found with the decreasing capability up to 66% where the higher percentage of N. nucifera flower powder was found to exert more prominent effect in lowering blood glucose level. During comparison to the control group, the above mentioned percentages of N. nucifera flowers powder was found to reduce the blood glucose level around 32.05% and 47.92% respectively. Although not prominent, but the data revealed that the sample was endowed with the body weight declining capability. Conclusion: Results of the experiments affirm that the flower of N. nucifera has potent hypoglycemic and hypolipidemic properties and might be useful in these patients.